A note on linear preservers of certain ranks of tensor products of matrices - Lim, Ming Huat (Taylor & Francis Ltd., 2015)
In this note, we give a simple proof as well as an extension of a very recent result of B. Zheng, J. Xu and A. Fosner concerning linear maps between vector spaces of complex square matrices that preserve the rank of tensor products of matrices by using a structure theorem of R. Westwick on linear maps between tensor product spaces that preserve non-zero decomposable elements.